Characterization of Urease from Providencia sp. LBBE and Its Application in Degrading Urea and Ethyl Carbamate in Rice Wine - Han Wang; Dandan Li; Sibao Zhu; Shuxian Guo; Jiahong Ding; Chuanchao Wu; Qingtao Liu (Fermentation, 2024)
Enzymatic degradation of the carcinogen ethyl carbamate (EC) and its precursor urea is a promising method for controlling EC levels in alcoholic beverages. However, limited enzymes with EC-hydrolyzing activity and low ethanol or acid tolerance hinder their practical application. Here, a new urease with urea- and EC-hydrolyzing activities from Providencia sp. LBBE was characterized. The enzyme displayed considerable ethanol tolerance, retaining 42.4% activity after 1 h of incubation with 30% (v/v) ethanol at 37 °C. It exhibited broad pH tolerance (pH 3.0–8.0), with optimal pH 7.0 for EC and 7.5 for urea. After treatment at pH 4.5 and 5.0, it retained 41.3% and 59.4% activity, respectively. The Km and Vmax for EC and urea at pH 4.5 were 515.6 mM, 33.9 µmol/(min⸱mg) and 32.0 mM, 263.6 µmol/(min⸱mg), respectively. Using 6000 U/L purified enzyme at 30 °C for 9 h, 49.8% and 81.6% of urea was removed from rice wine (pH 4.5 and 7.0), respectively. No appreciable reduction in EC was observed under identical conditions, which may be ascribed to the minimal EC affinity. This study contributes to the future realization of the effective control of EC content in alcoholic beverages.